Measuring Complexity of SAP Systems - Holub, Ilja; Bruckner, Tomas (Complex Systems Informatics and Modeling Quarterly, 2016)
The paper discusses the reasons of complexity rise in ERP system SAP R/3. It proposes a method for measuring complexity of SAP. Based on this method, the computer program in ABAP for measuring complexity of particular SAP implementation is proposed as a tool for keeping ERP complexity under control. The main principle of the measurement method is counting the number of items or relations in the system. The proposed computer program is based on counting of records in organization tables in SAP.